Effect of post-deposition annealing on composition and electrical properties of dc reactive magnetron sputtered Al2O3 thin films. (March 2014) - Prasanna, S.; Shaik, H.; Mohan Rao, G.; Vandana; Singh, P. K.; Jayakumar, S.; Balasundaraprabhu, R.
<x content-type="archive" xml:space="preserve">Abstract</x> We have investigated the effect of post-deposition annealing on the composition and electrical properties of alumina (Al2O3) thin films. Al2O3 were deposited on n-type Si <100> substrates by dc reactive magnetron sputtering. The films were subjected to post-deposition annealing at 623, 823 and 1023 K in vacuum. X-ray photoelectron spectroscopy results revealed that the composition improved with post-deposition annealing, and the film annealed at 1023 K became stoichiometric with an O/Al atomic ratio of 1·49. Al/Al2O3/Si metal–oxide–semiconductor (MOS) structures were then fabricated, and a correlation between the dielectric constant ϵr and interface charge density Qi with annealing conditions were studied. The dielectric constant of the Al2O3 thin films increased to 9·8 with post-deposition annealing matching the bulk value, whereas the oxide charge density decreased to 3·11×1011 cm−2. Studies on current–voltage IV characteristics indicated ohmic and Schottky type of conduction at lower electric fields (<0·16 MV cm−1) and space charge limited conduction at higher electric fields.